The conjure-man dies : a mystery tale of dark Harlem - Fisher, Rudolph, 1897-1934 (Library of Congress crime classics., 2022)
An unmissable entry in the esteemed Library of Congress Crime Classics, an exciting new classic mystery series created in exclusive partnership with the Library of Congress to highlight the best of American crime fiction. When the body of N'Gana Frimbo, the African conjure-man, is discovered in his consultation room, Perry Dart, one of Harlem's ten Black police detectives, is called in to investigate. Together with Dr Archer, a physician from across the street, Dart is determined to solve the baffling mystery, helped and hindered by Bubber Brown and Jinx Jenkins, local boys keen to clear themselves of suspicion of murder and undertake their own investigations. This groundbreaking mystery is the first ever to feature a Black detective and all Black characters, written by Black author Rudolph Fisher, who was a principal writer of the Harlem Renaissance.